Cone-beam Computed Tomography-based three-dimensional cephalometric analysis of mandible symmetry and the occlusal plane of adult patients with high-angle skeletal class III malocclusion and jaw deformity. (July 2021) - Teng, Caitian; Liu, Chao; Yu, Qing; Liu, Shu
Highlights: Study high-angle skeletal class III malocclusion with jaw deformity. Analyze the mandible symmetry and the occlusal plane by CBCT-based 3D cephalometric. The coefficient of variation of mandibular angle of jaw deformity was the largest. A linear relationship between mandibular deviation and the occlusal plane were found. Abstract: Objective: To use cone beam computed tomography (CBCT) scans to analyze mandibular symmetry, the occlusal plane and their correlations in patients with high-angle skeletal class III malocclusion and jaw deformity. Design: Reconstructed images simulated of CBCT data of 20 adult patients with high-angle skeletal class III malocclusion and jaw asymmetry (Experimental group) and 20 adult patients of skeletal class I with normal faces (Control group) were measured with a three-dimensional (3D) geometric morphological measurement system. Related landmarks, lines and planes were marked and relevant distances and angles of 3D craniofacial structures were measured. The Student t -test was performed to assess symmetry. With the help of the Pearson correlation and Linear regression, we explored the correlations and other relationships among them. Results: Compared with control group, the symmetrical differences in experimental group were concentrated in condyle, coracoid process, mandibular angle, mandibular first molar area and the chin (P < 0.05). A strong positive correlation was found between the degree of mandibular deviation and the inclination of the occlusal plane in the coronal position (r = 0.860, P < 0.001) and a linear relationship between them was found: Y = 1.300 + 0.419X (the inclination of occlusal plane was Y, and the mandibular deviation was X). Conclusions: Certain characteristics of mandibular symmetry and the occlusal plane were found in patients with high-angle skeletal class III malocclusion and jaw asymmetry. These findings provide references for doctors to pay attention to the degree and location of mandibular asymmetry and to determine the occlusal plane.